A Review of the Phytochemistry, Traditional Uses, and Biological Activities of the Genus Ballota and Otostegia - Rosselli, Sergio; Fontana, Gianfranco; Bruno, Maurizio (Planta Medica, 2019)
The 2 genera Ballota and Otostegia, belonging to the Lamiaceae family, are closely related taxonomically and found mainly in the Mediterranean area, Middle East, and North Africa. Since ancient times, they have been largely employed in traditional medicine for their biological properties such as antimicrobial, anti-inflammatory, antispasmodic, insecticidal, anti-malaria, etc. Phytochemical investigations of Ballota and Otostegia species have revealed that diterpenoids are the main constituents of the genera. A large number of flavonoids and other metabolites were also identified. This review, covering literature from 1911 up to 2018, includes traditional uses, chemical profiles (both of volatile and nonvolatile metabolites), and biological properties of all the taxa of these 2 genera studied to date.
Keywords: Ballota; Otostegia; secondary metabolites; antioxidant; antibacterial; antifungal